SANDY AND CLAY SOIL FERTILITY AFTER APPLICATION OF SOIL CONDITIONER FROM WATER HYACINTH (Eichhornia crassipes [mart.] solms) SHOOTS AND ROOTS - Munifatul Izzati (Indonesian Journal of Conservation, 2023)
ABSTRACT Water hyacinth is an aquatic plant that highly problematic. Its fast-growing will chock of many water bodies, including in Rawa Pening Lake. Researchers are trying to find its economic uses. This study is aimed to evaluate the use of water hyacinth shoot and root as a soil conditioner in improving the fertility of sandy and clay soil. We used sandy and clay soil as evaluated and two treatments of soil conditioner, using water hyacinth shoots and root dried powder The water hyacinth biomass taken from Rawa Pening lake was dried under the sun and smashed into powder. The mixed dried powder with sandy or clay soil was prepared in the plastic polybag in the proportion of 1:1. The experiment was using a complete randomized design (CRD). Pure sandy and clay soil without soil conditioner was used as controls. Mixed soil fertility was evaluated for soil organic matter, bacteria population, C: N ratio, and water holding capacity. Results indicated that water hyacinth shoots and roots significantly increased the organic matter and bacteria population in both, sandy and clay soil. The ratio of C: N was reduced significantly. Water holding capacity in sandy soil was significantly increased, while in clay soil was reduced. It is suggested that the addition of water hyacinth shoots and roots as soil conditioners will significantly improve sandy and clay soil fertility. Water hyacinth roots contribute to better soil fertility than its shoots.KEYWORDS Keywords: clay, fertility, sandy, soil, water-hyacinthÂ Â